Bad Beliefs Why They Happen to Good People - Levy, Neil (Oxford University Press, 2021)
Why do people come to reject climate science or the safety and efficacy of vaccines, in defiance of the scientific consensus? A popular view explains bad beliefs like these as resulting from a range of biases that together ensure that human beings fall short of being genuinely rational animals. This book presents an alternative account. It argues that bad beliefs arise from genuinely rational processes. We've missed the rationality of bad beliefs because we've failed to recognize the ubiquity of the higher-order evidence that shapes beliefs, and the rationality of being guided by this evidence. The book argues that attention to higher-order evidence should lead us to rethink both how minds are best changed and the ethics of changing them: we should come to see that nudging-at least usually-changes belief (and behavior) by presenting rational agents with genuine evidence, and is therefore fully respectful of intellectual agency. We needn't rethink Enlightenment ideals of intellectual autonomy and rationality, but we should reshape them to take account of our deeply social epistemic agency.